Nonaqueous electrolyte for lithium secondary battery and lithium secondary battery containing same
The non-aqueous electrolyte for lithium secondary batteries, featuring an oligomer with nitrile and aromatic groups, addresses transition metal elution and anion instability, improving high-temperature performance and cycle stability.
Patent Information
- Application Number
- JP2023567025
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-06
- Filing Date
- 2022-09-07
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2042-09-07
AI Technical Summary
Lithium secondary batteries face issues with transition metal elution and anion instability due to the decomposition of LiPF6 in non-aqueous electrolytes, leading to safety concerns and reduced performance at high temperatures.
A non-aqueous electrolyte for lithium secondary batteries containing an oligomer derived from a monomer with a nitrile and aromatic hydrocarbon group, which forms a stable film on electrodes, chelates metal ions, and forms complexes with anions to suppress side reactions.
The electrolyte improves high-temperature storage performance and cycle capacity retention by stabilizing anions and preventing metal elution, enhancing the battery's stability and safety.
Smart Images

Figure 0007618062000001 
Figure 0007618062000002 
Figure 0007618062000003
Abstract
Description
[Technical Field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0120379, filed September 9, 2021, and Korean Patent Application No. 10-2022-0113086, filed September 6, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a non-aqueous electrolyte for a lithium secondary battery containing an additive capable of suppressing the elution of transition metals and stabilizing anions generated from a lithium salt, and to a lithium secondary battery containing the same. [Background technology]
[0003] In recent years, with the development of the information society, the development of personal IT devices and computer networks has led to an increase in society's overall dependence on electrical energy, creating a demand for technological development to efficiently store and utilize electrical energy.
[0004] Lithium secondary batteries are the most suitable technology for a wide range of applications. Compared to lead batteries and nickel-cadmium batteries, they can be made small enough to be used in personal IT devices, and they have high energy density, high operating voltage, and the ability to achieve high capacity. As a result, they are used not only as power sources for notebook computers and mobile phones, but also in electric vehicles and power storage devices.
[0005] A lithium-ion battery is broadly composed of a positive electrode made of a transition metal oxide containing lithium, a negative electrode capable of storing lithium, a non-aqueous electrolyte that acts as a medium for transferring lithium ions, and a separator. In particular, non-aqueous electrolytes that use a non-aqueous organic solvent containing dissolved lithium salts such as LiPF6 as their main component are known to be a factor that has a significant impact on the stability and safety of the battery.
[0006] On the other hand, when the lithium salt LiPF6 in the non-aqueous electrolyte decomposes during battery operation, it generates LiF and PF5, which react with the non-aqueous organic solvent to accelerate depletion of the non-aqueous organic solvent or generate a large amount of gas, resulting in deterioration of high-temperature performance and safety. Furthermore, lithium-ion batteries have the problem that the deterioration of the positive electrode during battery operation progresses, leading to the elution of transition metals and the promotion of side reactions such as the reduction of the eluted transition metals at the negative electrode.
[0007] Therefore, there is a need for the development of a non-aqueous electrolyte that can form a stable coating on the surface of the electrode, prevent side reactions between the non-aqueous electrolyte and the electrode, and suppress the elution of transition metals. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made to solve the above-mentioned problems, and aims to provide a nonaqueous electrolyte solution for a lithium secondary battery that contains an oligomer obtained from a monomer based on an acrylate structure that contains at least one functional group selected from a nitrile group (—CN) and an aromatic hydrocarbon group, thereby making it possible to suppress the elution of transition metals and stabilize anions generated from lithium salts.
[0009] Another object of the present invention is to provide a lithium secondary battery containing the nonaqueous electrolyte solution for lithium secondary batteries, which has improved cycle characteristics and high-temperature storage characteristics. [Means for solving the problem]
[0010] According to one embodiment, the present invention comprises: A lithium salt, a non-aqueous organic solvent; and an oligomer including a repeating unit derived from a monomer represented by the following chemical formula 1 and a repeating unit derived from a monomer represented by the following chemical formula 2:
[0011] [ka]
[0012] In the above Chemical Formula 1, R' is hydrogen or an alkyl group having 1 to 3 carbon atoms; R1 is an alkylene group having 1 to 20 carbon atoms.
[0013] [ka]
[0014] In the above Chemical Formula 2, R'' is hydrogen or an alkyl group having 1 to 3 carbon atoms; R2 is a direct bond or an alkylene group having 1 to 5 carbon atoms; A is an aromatic hydrocarbon group or a heteroaromatic hydrocarbon group.
[0015] According to another embodiment, the present invention provides a lithium secondary battery including: a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator interposed between the negative electrode and the positive electrode; and the nonaqueous electrolyte solution for a lithium secondary battery according to the present invention. [Effects of the Invention]
[0016] The nonaqueous electrolyte solution for a lithium secondary battery of the present invention contains an oligomer obtained from a monomer based on an acrylate structure containing at least one functional group selected from a nitrile group (—CN) and an aromatic hydrocarbon group, and is therefore capable of forming a stable coating on the surfaces of the negative electrode and positive electrode, chelating eluted metal ions, and forming a complex with an anion dissociated from a lithium salt to suppress side reactions caused by the anion.
[0017] Therefore, by using the nonaqueous electrolyte for a lithium secondary battery of the present invention, it is possible to realize a lithium secondary battery having improved high-temperature storage performance and cycle capacity retention rate during high-voltage operation. DETAILED DESCRIPTION OF THE INVENTION
[0018] The present invention will now be described in more detail. The terms and words used in this specification and claims should not be interpreted in a limited way to their ordinary or dictionary meanings, but should be interpreted in a way that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best explain their inventions.
[0019] Meanwhile, in this specification, "*" means a site that is connected to the main chain in an oligomer or to a bond such as another monomer, substituent, or terminal group in a chemical formula.
[0020] Nonaqueous electrolyte for lithium secondary batteries According to one embodiment, the present invention provides a non-aqueous electrolyte for a lithium secondary battery. The nonaqueous electrolyte for a lithium secondary battery is A lithium salt, a non-aqueous organic solvent; and an oligomer containing a repeating unit derived from a monomer represented by the following chemical formula 1 and a repeating unit derived from a monomer represented by the following chemical formula 2.
[0021] [ka]
[0022] In the above Chemical Formula 1, R' is hydrogen or an alkyl group having 1 to 3 carbon atoms; R1 is an alkylene group having 1 to 20 carbon atoms.
[0023] [ka]
[0024] In the above Chemical Formula 2, R'' is hydrogen or an alkyl group having 1 to 3 carbon atoms; R2 is a direct bond or an alkylene group having 1 to 5 carbon atoms; A is an aromatic hydrocarbon group or a heteroaromatic hydrocarbon group.
[0025] (1) Lithium salt First, the lithium salt will be described as follows. The lithium salt may be any one that is commonly used in electrolytes for lithium secondary batteries without any limitation. For example, the cation may be Li + and the anion is F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , B 10 Cl 10 - , AlCl4 - , AlO4 - , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CF3(CF2)7SO3 - , and SCN- The composition may include at least one selected from the group consisting of:
[0026] Specifically, the lithium salts include LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 The lithium salt may include a single substance or a mixture of two or more substances selected from the group consisting of LiAlCl, LiAlO, LiPF, LiCF, SO, LiCH, CO, LiCF, CO, LiAsF, LiSbF, LiCH, SO, LiN(SOF) (lithium bis(fluorosulfonyl)imide, LiFSI), LiN(SOCF) (lithium bis(pentafluoroethanesulfonyl)imide, LiBETI), and LiN(SOCF) (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI). In addition to the lithium salts listed above, any lithium salt commonly used in electrolytes for lithium secondary batteries may be used without limitation. Specifically, the lithium salt may include LiPF.
[0027] The lithium salt may be varied as appropriate within a range that is normally usable, but in order to obtain an optimal effect of forming a corrosion-preventing coating on the electrode surface, it may be contained in the electrolyte at a concentration of 0.8 M to 3.0 M, specifically 1.0 M to 3.0 M. When the concentration of the lithium salt satisfies this range, the viscosity of the nonaqueous electrolyte can be controlled to achieve optimal impregnation, and the mobility of lithium ions can be improved, resulting in improved capacity characteristics and cycle characteristics of the lithium secondary battery.
[0028] (2) Non-aqueous organic solvent The non-aqueous organic solvent is described below. The non-aqueous organic solvent may be any of various non-aqueous organic solvents commonly used in non-aqueous electrolytes, and is not limited to any particular type as long as it can minimize decomposition due to oxidation reactions during the charge / discharge process of the secondary battery and exhibit desired properties together with the additives.
[0029] Specifically, the non-aqueous organic solvent may include at least one of a high-viscosity cyclic carbonate-based compound having a high dielectric constant and capable of dissociating lithium salts, and a linear carbonate-based compound having a low viscosity and a low dielectric constant.
[0030] The cyclic carbonate compound may include at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate, and may include ethylene carbonate.
[0031] The linear carbonate compound may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, and specifically may include ethyl methyl carbonate (EMC).
[0032] In the present invention, the cyclic carbonate compound and the linear carbonate compound may be mixed and used. In this case, the mixing ratio of the cyclic carbonate compound to the linear carbonate compound may be a volume ratio of 10:90 to 80:20, specifically a volume ratio of 30:70 to 50:50.
[0033] When the mixing ratio of the cyclic carbonate compound to the linear carbonate compound satisfies the above range, a non-aqueous electrolyte solution having higher electrical conductivity can be prepared.
[0034] Meanwhile, in the present invention, in order to improve the shortcomings of the carbonate-based compound and to increase safety during high temperature and high voltage operation, a propionate compound may be further mixed as the non-aqueous organic solvent.
[0035] The propionate compound may include at least one selected from the group consisting of methyl propionate, ethyl propionate (EP), propyl propionate, and butyl propionate, and specifically may include at least one of ethyl propionate and propyl propionate.
[0036] Meanwhile, in the non-aqueous electrolyte solution for a lithium secondary battery of the present invention, the remaining components excluding the non-aqueous organic solvent, such as the lithium salt, the oligomer, and optional additives, may all be non-aqueous organic solvents unless otherwise specified.
[0037] (C) Oligomer The nonaqueous electrolyte for a lithium secondary battery of the present invention contains an oligomer. The oligomer may include a repeating unit derived from a monomer represented by the following Chemical Formula 1 and a repeating unit derived from a monomer represented by the following Chemical Formula 2:
[0038] [ka]
[0039] In the above Chemical Formula 1, R' is hydrogen or an alkyl group having 1 to 3 carbon atoms; R1 is an alkylene group having 1 to 20 carbon atoms.
[0040] [ka]
[0041] In the above Chemical Formula 2, R'' is hydrogen or an alkyl group having 1 to 3 carbon atoms; R2 is a direct bond or an alkylene group having 1 to 5 carbon atoms; A is an aromatic hydrocarbon group or a heteroaromatic hydrocarbon group.
[0042] The oligomer of the present invention contains a repeating unit structure derived from the monomer represented by Chemical Formula 1, which contains a terminal nitrile group based on an acrylate structure, and thus can form a stable coating on the surface of the positive electrode and can control the elution of metal ions from the positive electrode due to its strong bonding force with the metal ions, thereby improving the high-temperature durability, high-temperature storage characteristics, and high-temperature stability of the battery.
[0043] In addition, the oligomer of the present invention includes a repeating unit structure derived from the monomer represented by Chemical Formula 2, which includes a terminal aromatic hydrocarbon group or heteroaromatic hydrocarbon group based on an acrylate structure, and thus coordinates with a thermal decomposition product of a lithium salt such as LiPF6 or an anion dissociated from the lithium salt to form a complex. This stabilizes the thermal decomposition product of the lithium salt or the anion dissociated from the lithium salt, thereby suppressing side reactions between the thermal decomposition product of the lithium salt and the electrolyte for a lithium secondary battery.
[0044] The nonaqueous electrolyte containing the oligomer of the present invention can suppress side reactions in the electrolyte and form a robust SEI film with low resistance, thereby preventing side reactions between the electrode and the electrolyte and suppressing gas generation.Furthermore, the internal resistance of the battery can be reduced, significantly lowering the failure rate and improving the cycle characteristics of the lithium secondary battery.
[0045] Such an oligomer of the present invention may be an oligomer represented by the following chemical formula 3.
[0046] [ka]
[0047] In the above Chemical Formula 3, R' and R'' are each independently hydrogen or an alkyl group having 1 to 3 carbon atoms; R1 is an alkylene group having 1 to 20 carbon atoms, R2 is a direct bond or an alkylene group having 1 to 5 carbon atoms; A is an aromatic hydrocarbon group or a heteroaromatic hydrocarbon group; The molar ratio of m:n is 1:99 to 99:1.
[0048] Specifically, in the above chemical formula 3, R1 may be an alkylene group having 1 to 10 carbon atoms, and preferably an alkylene group having 1 to 5 carbon atoms. In addition, in the above chemical formula 3, R2 may be an alkylene group having 1 to 3 carbon atoms.
[0049] The aromatic hydrocarbon group may be at least one of benzene, naphthalene, and anthracene, and may specifically be benzene. The heteroaromatic hydrocarbon group may be at least one of furan, pyrrole, imidazole, pyridine, pyrazine, pyrimidine, pyridazine, 1,2,3-triazine, 1,2,4-triazine, and 1,3,5-triazine, and specifically may be at least one of pyrrole, imidazole, pyridine, pyrazine, pyrimidine, and pyridazine containing nitrogen as a hetero element.
[0050] Preferably, the oligomer may be at least one selected from the group consisting of oligomers represented by the following Chemical Formula 3-1 and Chemical Formula 3-2.
[0051] [ka]
[0052] In the above chemical formula 3-1, The molar ratio of m1:n1 is 1:99 to 99:1.
[0053] [ka]
[0054] In the above chemical formula 3-2, The molar ratio of m2:n2 is 1:99 to 99:1.
[0055] The weight-average molecular weight (Mw) of the oligomer of the present invention may be adjusted by the number of repeating units and may be about 3,000 g / mol to 300,000 g / mol, specifically 10,000 g / mol to 100,000 g / mol. When the weight-average molecular weight of the oligomer satisfies this range, the physical properties of the oligomer itself are prevented from becoming rigid, and the affinity with the non-aqueous electrolyte solvent is increased, allowing for easy dissolution, and the formation of a uniform and excellent non-aqueous electrolyte can be expected.
[0056] The weight-average molecular weight can be measured using a gel permeation chromatography (GPC) device, and unless otherwise specified, the molecular weight refers to the weight-average molecular weight. For example, in the present invention, the measurement is performed using an Agilent 1200 series GPC condition, and the column used may be an Agilent PL mixed B column, and the solvent may be THF or DMF. On the other hand, in order to satisfy the weight average molecular weight of the oligomer, the molar ratio of m:n may be 1:99 to 99:1, specifically 1:99 to 30:70.
[0057] The oligomer may be contained in an amount of 0.1 wt % to 25 wt % based on the total weight of the non-aqueous electrolyte for a lithium secondary battery. When the oligomer is contained in this content range, an effect of improving anion stabilization and an effect of forming a stable coating can be achieved.
[0058] When the oligomer content is 0.1 wt % or more, anion stabilization can be more stably maintained through the formation of a complex with anions during the battery's operation, and metal ion elution can be suppressed through the formation of a film due to adsorption on the positive electrode surface and the formation of a complex with metal ions. Furthermore, when the oligomer content is 25 wt % or less, an increase in the viscosity of the electrolyte due to excess compounds can be prevented, ion mobility within the battery can be improved, and cell swelling can be significantly suppressed. Excessive film formation can be suppressed, effectively preventing an increase in battery resistance, thereby preventing a decrease in capacity and cycle characteristics.
[0059] Specifically, the oligomer may be contained in an amount of 0.5 to 20% by weight, preferably 0.5 to 15% by weight, based on the total weight of the non-aqueous electrolyte for lithium secondary batteries.
[0060] (4) Other additives In addition, the nonaqueous electrolyte for a lithium secondary battery of the present invention may further contain other additives in addition to the two types of nitrile-based additives, as necessary, to prevent the nonaqueous electrolyte from being decomposed in a high-power environment, which may lead to the collapse of the negative electrode, and to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge prevention, and the effect of suppressing battery expansion at high temperatures.
[0061] Examples of such other additives include at least one selected from the group consisting of cyclic carbonate-based compounds, halogen-substituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based or phosphite-based compounds, borate-based compounds, nitrile-based compounds, benzene-based compounds, amine-based compounds, silane-based compounds, and lithium salt-based compounds.
[0062] Examples of the cyclic carbonate compounds include vinylene carbonate (hereinafter referred to as "VC") and vinyl ethylene carbonate (VEC). Examples of the halogen-substituted carbonate compounds include fluoroethylene carbonate (FEC).
[0063] The sultone compound may be, for example, at least one compound selected from the group consisting of 1,3-propane sultone (hereinafter referred to as "1,3-PS"), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.
[0064] The sulfate-based compound may be, for example, ethylene sulfate (hereinafter referred to as "Esa"), trimethylene sulfate (TMS), or methyl trimethylene sulfate (MTMS).
[0065] The phosphate-based or phosphite-based compound may be, for example, at least one selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite.
[0066] Examples of the borate-based compound include tetraphenylborate, lithium oxalyldifluoroborate (LiODFB) which can form a coating on the surface of the negative electrode, and lithium bisoxalateborate (LiB(C2O4)2, LiBOB).
[0067] The nitrile compound may include at least one compound selected from the group consisting of compounds other than 1,4-dicyano-2-butene and 1,3,5-cyclohexanetricarbonitrile, such as succinonitrile, pimelonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile. The benzene-based compound may be fluorobenzene or the like.
[0068] The amine-based compound may be triethanolamine, ethylenediamine, or the like, and the silane-based compound may be tetravinylsilane, or the like. The lithium salt-based compound is a compound different from the lithium salt contained in the non-aqueous electrolyte, and examples thereof include LiPO2F2 and LiBF4.
[0069] Among these other additives, in order to form a stronger SEI coating on the surface of the negative electrode, other additives that are effective in forming a coating on the surface of the negative electrode, specifically at least one selected from the group consisting of VC, 1,3-PS, Esa, vinyl ethylene carbonate, fluoroethylene carbonate (FEC), lithium oxalyl difluoroborate (LiODFB), 1,4-dicyano-2-butene, and 1,3,5-cyclohexanetricarbonitrile, may be included.
[0070] The other additives may be used as a mixture of two or more compounds, and may be contained in the non-aqueous electrolyte solution in an amount of 0.01 to 50 wt %, specifically 0.01 to 10 wt %, and preferably 0.05 to 5 wt %. When the amount is within the above range, the effect of improving the cycle characteristics of the other additives can be fully realized, while preventing the remaining unreacted material of the other additives and the occurrence of excessive side reactions due to the addition of an excessive amount, which is preferable.
[0071] Lithium secondary battery Another embodiment of the present invention provides a lithium secondary battery including the nonaqueous electrolyte for a lithium secondary battery of the present invention. Specifically, the lithium secondary battery may include a positive electrode, a negative electrode, and the nonaqueous electrolyte for a lithium secondary battery described above.
[0072] Meanwhile, the lithium secondary battery of the present invention can be manufactured by forming an electrode assembly in which a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode are sequentially stacked, housing the electrode assembly in a battery case, and then introducing the nonaqueous electrolyte of the present invention into the battery case.
[0073] The method for manufacturing the lithium secondary battery of the present invention may be carried out by a conventional method well known in the art, and will be described in detail below.
[0074] (1) Positive electrode The positive electrode according to the present invention may include a positive electrode active material layer containing a positive electrode active material, and if necessary, the positive electrode active material layer may further include a conductive material and / or a binder.
[0075] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and specifically may include a lithium composite metal oxide represented by the following chemical formula 4, which includes lithium and at least one metal selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), iron (Fe), and aluminum (Al).
[0076] [Chemical formula 4] Li1+a Ni x Co y M 1 z M 2 w O2
[0077] In the chemical formula 4, M 1 is Mn, Al, or a combination thereof, M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, Mg, Ca, and Sr, and 0 ≦ a ≦ 0.5, 0 < x ≦ 1.0, 0 < y ≦ 0.4, 0 < z ≦ 0.4, 0 ≦ w ≦ 0.1.
[0078] The 1 + a represents the atomic fraction of lithium in the lithium transition metal oxide, and 0 ≦ a ≦ 0.5, preferably 0 ≦ a ≦ 0.2, more preferably 0 ≦ a ≦ 0.1 may be applicable.
[0079] The x represents the atomic fraction of nickel in all transition metal elements in the lithium transition metal oxide, and 0 < x ≦ 1.0, specifically 0.55 < x < 1.0, more specifically 0.6 ≦ x ≦ 0.98, even more specifically 0.6 ≦ x ≦ 0.95 may be applicable.
[0080] The y represents the atomic fraction of cobalt in all transition metal elements in the lithium transition metal oxide, and 0 < y ≦ 0.4, specifically 0 < y ≦ 0.3, more specifically 0.05 ≦ y ≦ 0.3 may be applicable.
[0081] The z represents the atomic fraction of the M 1 element in all transition metal elements in the lithium transition metal oxide, and 0 < z ≦ 0.4, preferably 0 < z ≦ 0.3, more preferably 0.01 ≦ z ≦ 0.3 may be applicable.
[0082] The w represents the atomic fraction of the M 2 element in all transition metal elements in the lithium transition metal oxide, and 0 < w ≦ 0.1, preferably 0 < w ≦ 0.05, more preferably 0 < w ≦ 0.02.
[0083] Specifically, the positive electrode active material is Li(Ni) having a Ni content of 0.55 atm % or more in order to realize a high-capacity battery. 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, Li(Ni 0.7 Mn 0.2 Co 0.1 )O2, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, Li(Ni 0.86 Mn 0.07 Co 0.05 Al 0.02 )O2, or Li(Ni 0.90 Mn 0.05 Co 0.05 )O2.
[0084] On the other hand, when high content nickel (Hi-Ni) with Ni content exceeding 0.55 is used as the lithium transition metal oxide, Li +1 ions and Ni +2 Because the size of the ions is similar, Li +1 ions and Ni +2 Cation mixing, which changes the position of ions, occurs. Specifically, nickel transition metals with d-orbitals should form a regular octahedral structure when coordinated under high temperature conditions, depending on the oxidation state of Ni contained in the positive electrode active material. However, external energy supply changes the order of energy levels, or a heterogeneous reaction that changes the oxidation state causes a twisted octahedron to form, resulting in deformation and collapse of the positive electrode active material's crystal structure. Furthermore, during high-temperature storage, side reactions between the positive electrode active material and the electrolyte can cause transition metals, particularly nickel metal, to leach from the positive electrode active material, or other side reactions can occur, resulting in electrolyte depletion and structural collapse of the positive electrode active material, resulting in a decline in the performance of secondary batteries.
[0085] In the present invention, such problems can be improved by using together a non-aqueous electrolyte containing an additive having a specific configuration and a positive electrode containing a high-content nickel (Hi-Ni) transition metal oxide as a positive electrode active material. That is, a firm ion-conductive film is formed on the surface of the positive electrode by the non-aqueous electrolyte of the present invention, and Li +1 ions and Ni +2 ion cation mixing phenomenon is suppressed, side reactions between the positive electrode and the electrolyte, metal dissolution phenomenon, etc. can be effectively suppressed, and the structural instability of the high-capacity electrode can be alleviated. Therefore, a sufficient amount of nickel transition metal for ensuring the capacity of the lithium secondary battery can be secured, so that the energy density can be increased and the output characteristics can be improved.
[0086] On the other hand, the positive electrode active material of the present invention, depending on the use of the secondary battery, together with the lithium composite metal oxide represented by the chemical formula 4, lithium-manganese-based oxides (for example, LiMnO2, LiMn2O4, etc.), lithium-cobalt-based oxides (for example, LiCoO2, etc.), lithium-nickel-based oxides (for example, LiNiO2, etc.), lithium-nickel-manganese-based oxides (for example, LiNi 1-Y Mn Y O2 (0 < Y < 1), LiMn 2-z Ni z O4 (0 < Z < 2), lithium-nickel-cobalt-based oxides (for example, LiNi 1-Y1 Co Y1 O2 (0 < Y1 < 1), lithium-manganese-cobalt-based oxides (for example, LiCo 1-Y2 Mn Y2 O2 (0 < Y2 < 1), LiMn 2-z1 Co z1 O4 (0 < Z1 < 2), or Li(Ni p1 Co q1 Mn r2 )O4 (0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), etc. may be used in combination.
[0087] The positive electrode active material may be contained in an amount of 80 to 98 wt %, more specifically 85 to 98 wt %, based on the total weight of the positive electrode active material layer. When the positive electrode active material is contained in this range, excellent capacity characteristics can be exhibited.
[0088] Next, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause chemical changes in the constructed battery and has electronic conductivity. Specific examples include carbon powders such as carbon black, acetylene black (or denka black), ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, and graphite with highly developed crystalline structures; conductive fibers such as carbon fiber and metal fiber; conductive powders such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 10% by weight, preferably 0.1 to 5% by weight, based on the total weight of the positive electrode active material layer.
[0089] The binder serves to improve adhesion between particles of the positive electrode active material and the adhesive strength between the positive electrode active material and the current collector. Examples of such binders include fluororesin-based binders including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber; cellulose-based binders including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders including polyvinyl alcohol; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders, which may be used alone or in combination of two or more. The binder may be contained in an amount of 0.1 to 15% by weight, preferably 0.1 to 10% by weight, based on the total weight of the positive electrode active material layer.
[0090] The positive electrode of the present invention may be manufactured by a method known in the art, such as by dissolving or dispersing a positive electrode active material, a binder, and / or a conductive material in a solvent to prepare a positive electrode slurry, coating the slurry on a positive electrode current collector, and then drying and rolling the slurry to form an active material layer, or by casting the positive electrode active material layer on a separate support, peeling off the support, and laminating the resulting film on a positive electrode current collector.
[0091] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and is conductive. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like may be used. The positive electrode current collector may typically have a thickness of 3 to 500 μm, and the surface of the current collector may be formed with fine irregularities to enhance the adhesive strength of the positive electrode material. The positive electrode current collector may be used in various forms, such as a film, sheet, foil, mesh, porous material, foam, or nonwoven fabric.
[0092] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination. The amount of the solvent used is not particularly limited as long as it can be adjusted to an appropriate viscosity for the cathode composite, taking into consideration the coating thickness of the cathode composite, production yield, workability, etc.
[0093] (2) Negative electrode Next, the negative electrode will be described. The negative electrode according to the present invention includes a negative electrode active material layer containing a negative electrode active material, and the negative electrode active material layer may further include a conductive material and / or a binder, as necessary.
[0094] The negative electrode active material may be any of various negative electrode active materials used in the art, such as a carbon-based negative electrode active material, a silicon-based negative electrode active material, or a mixture thereof.
[0095] According to one embodiment, the negative electrode active material may include a carbon-based negative electrode active material, and the carbon-based negative electrode active material may include various carbon-based negative electrode active materials used in the art, such as graphite-based materials such as natural graphite, artificial graphite, and Kish graphite; high-temperature-calcined carbon such as pyrolytic carbon, mesophase pitch-based carbon fiber, mesocarbon microbeads, mesophase pitches, and petroleum or coal tar pitch-derived cokes; soft carbon; and hard carbon. The shape of the carbon-based negative electrode active material is not particularly limited, and various shapes such as amorphous, plate-like, flake-like, spherical, and fibrous may be used.
[0096] Preferably, the negative electrode active material may be at least one carbon-based negative electrode active material selected from natural graphite and artificial graphite, or both natural graphite and artificial graphite may be used to increase the adhesive strength with the current collector and suppress detachment of the active material.
[0097] According to another embodiment, the negative electrode active material may include a silicon-based negative electrode active material in addition to the carbon-based negative electrode active material. The silicon-based negative electrode active material is, for example, metal silicon (Si), silicon oxide (SiO x, where 0 < x < 2), may contain one or more selected from the group consisting of silicon carbide (SiC), and Si - Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si). As the element Y, it may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db (Dubnium), Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0098] Since the silicon - based negative electrode active material exhibits higher capacity characteristics than the carbon - based negative electrode active material, when further containing the silicon - based negative electrode active material, even more excellent capacity characteristics can be obtained. However, in the case of a negative electrode containing a silicon - based negative electrode active material, compared with a graphite negative electrode, the SEI film contains even more components rich in oxygen (O - rich). The SEI film containing oxygen - rich components tends to be more easily decomposed when a Lewis acid such as HF or PF5 is present in the electrolyte. Therefore, in the case of a negative electrode containing a silicon - based negative electrode active material, in order to maintain a stable SEI film, it is necessary to suppress the generation of Lewis acids such as HF and PF5 in the electrolyte or remove (or scavenge) the generated Lewis acids. The non - aqueous electrolyte according to the present invention forms stable coatings on the positive and negative electrodes and contains an electrolyte additive excellent in the effect of removing Lewis acids, so that the decomposition of the SEI film can be effectively suppressed when using a negative electrode containing a silicon - based active material.
[0099] Meanwhile, the mixing ratio of the silicon-based negative electrode active material to the carbon-based negative electrode active material may be 3:97 to 99:1 by weight, preferably 5:95 to 15:85. When the mixing ratio of the silicon-based negative electrode active material to the carbon-based negative electrode active material satisfies this range, the volume expansion of the silicon-based negative electrode active material is suppressed while improving the capacity characteristics, and excellent cycle performance can be ensured.
[0100] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer. When the content of the negative electrode active material is in this range, excellent capacity characteristics and electrochemical characteristics can be obtained.
[0101] The conductive material is a component for further improving the conductivity of the negative electrode active material and may be added in an amount of 10 wt % or less, preferably 5 wt % or less, based on the total weight of the negative electrode active material layer. The conductive material is not particularly limited as long as it does not induce chemical changes in the battery and is conductive. Examples of such conductive materials include carbon powders such as carbon black, acetylene black (or denka black), ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, and graphite, each having a highly developed crystalline structure; conductive fibers such as carbon fiber and metal fiber; conductive powders such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0102] The binder is a component that aids in bonding between the conductive material, active material, and current collector, and is typically added in an amount of 0.1 to 10 wt % based on the total weight of the negative electrode active material layer. Examples of binders include fluororesin-based binders such as polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders such as styrene butadiene rubber (SBR), acrylonitrile butadiene rubber, and styrene-isoprene rubber; cellulose-based binders such as carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders such as polyvinyl alcohol; polyolefin-based binders such as polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders. The binder may be contained in an amount of 0.1 to 15% by weight, preferably 0.1 to 10% by weight, based on the total weight of the negative electrode active material layer.
[0103] The negative electrode may be manufactured by a method known in the art, for example, by coating a negative electrode slurry prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material in a solvent, on a negative electrode current collector, followed by rolling and drying to form an active material layer, or by casting the negative electrode active material layer on a separate support, peeling off the support, and laminating the resulting film on the negative electrode current collector.
[0104] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and examples thereof include copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surfaces treated with carbon, nickel, titanium, silver, or the like, and aluminum-cadmium alloys. The negative electrode current collector typically has a thickness of 3 μm to 500 μm, and, like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to enhance the binding strength of the negative electrode active material. The negative electrode current collector may be used in various forms, such as a film, sheet, foil, mesh, porous material, foam, or nonwoven fabric.
[0105] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination. The amount of the solvent used is not particularly limited as long as it is adjusted to an appropriate viscosity for the negative electrode slurry, taking into consideration the coating thickness of the negative electrode composite, production yield, workability, etc.
[0106] (3) Separator The lithium secondary battery according to the present invention includes a separator between the positive electrode and the negative electrode.
[0107] The separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is normally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to the ion movement of lithium salts and excellent ability to retain moisture in the electrolyte.
[0108] Specifically, the separator may be a porous polymer film, such as a porous polymer film made from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof. A conventional porous nonwoven fabric, such as a nonwoven fabric made from high-melting-point glass fiber or polyethylene terephthalate fiber, may also be used. To ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material may also be used, and may be selectively used as a single-layer or multi-layer structure.
[0109] The lithium secondary battery according to the present invention can be usefully used in portable devices such as mobile phones, notebook computers, and digital cameras, and in electric vehicles such as hybrid electric vehicles (HEVs).
[0110] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0111] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also as a unit battery in a medium- to large-sized battery module including a plurality of battery cells.
[0112] The present invention will be described in detail below with reference to examples. However, the examples of the present invention may be modified into various other forms, and the scope of the present invention should not be construed as being limited to the examples described below. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.
[0113] Example Example 1 (Manufacturing non-aqueous electrolytes for lithium secondary batteries) LiPF6 was dissolved in a non-aqueous organic solvent containing ethylene carbonate (EC):ethyl methyl carbonate (EMC) in a volume ratio of 30:70 to a concentration of 1.0 M, and then 0.5 wt% of an oligomer represented by Chemical Formula 3-1 (molar ratio of m1:n1: 20:80, weight average molecular weight: 100,000 g / mol) and 3.0 wt% of other additives (weight ratio of VC:1,3-PS:Esa = 1.5:0.5:1) were added to prepare a non-aqueous electrolyte for a lithium secondary battery (see Table 1 below).
[0114] (Lithium secondary battery manufacturing) Cathode active material (Li(Ni) 0.8 Mn 0.1 Co 0.1 )O2), conductive material (carbon black), and binder (polyvinylidene fluoride) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 97.5:1:1.5 to prepare a positive electrode slurry (solid content: 50 wt%). The positive electrode slurry was applied to a 12 μm-thick positive electrode current collector (aluminum (Al) thin film), dried, and roll-pressed to prepare a positive electrode.
[0115] Anode active material (artificial graphite:SiO = 90:10 weight ratio), binder (SBR-CMC), and conductive material (carbon black) were mixed with water as a solvent in a weight ratio of 95:3.5:1.5 to prepare anode slurry (solid content: 60 wt%). The anode slurry was applied to a 6 μm-thick copper (Cu) thin film as anode current collector, followed by drying and roll pressing to prepare anode.
[0116] In a dry room, an electrode assembly was fabricated by interposing a polyolefin-based porous separator coated with inorganic particles (Al2O3) between the fabricated positive electrode and negative electrode. The assembled electrode assembly was then placed in a pouch-type battery case, and the non-aqueous electrolyte for lithium secondary batteries was injected to fabricate a pouch-type lithium secondary battery.
[0117] Example 2. A non-aqueous electrolyte for a lithium secondary battery and a lithium secondary battery including the same were prepared in the same manner as in Example 1, except that LiPF was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and 5.0 wt % of an oligomer represented by Chemical Formula 3-1 (molar ratio of m1:n1: 20:80, weight average molecular weight: 100,000 g / mol) and 3.0 wt % of other additives (weight ratio of VC:1,3-PS:Esa = 1.5:0.5:1) were added to prepare a non-aqueous electrolyte for a lithium secondary battery (see Table 1 below).
[0118] Example 3 A non-aqueous electrolyte for a lithium secondary battery and a lithium secondary battery including the same were prepared in the same manner as in Example 1, except that LiPF was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 10.0 wt % of an oligomer represented by Chemical Formula 3-1 (molar ratio of m1:n1: 20:80, weight average molecular weight: 100,000 g / mol) and 3.0 wt % of other additives (weight ratio of VC:1,3-PS:Esa = 1.5:0.5:1) were added to prepare a non-aqueous electrolyte for a lithium secondary battery (see Table 1 below).
[0119] Example 4. A non-aqueous electrolyte for a lithium secondary battery and a lithium secondary battery including the same were prepared in the same manner as in Example 1, except that LiPF was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 30.0 wt % of an oligomer represented by Chemical Formula 3-1 (molar ratio of m1:n1: 20:80, weight average molecular weight: 100,000 g / mol) and 3.0 wt % of other additives (weight ratio of VC:1,3-PS:Esa = 1.5:0.5:1) were added to prepare a non-aqueous electrolyte for a lithium secondary battery (see Table 1 below).
[0120] Comparative Example 1 A non-aqueous electrolyte for a lithium secondary battery and a lithium secondary battery including the same were manufactured in the same manner as in Example 1, except that LiPF was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 3.0 wt % of other additives (weight ratio of VC:1,3-PS:Esa = 1.5:0.5:1) were added to prepare a non-aqueous electrolyte for a lithium secondary battery (see Table 1 below).
[0121] Comparative Example 2 A non-aqueous electrolyte for a lithium secondary battery and a lithium secondary battery including the same were manufactured in the same manner as in Example 1, except that LiPF was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and 0.5 wt % of an oligomer represented by the following Chemical Formula 5 (a:b molar ratio: 20:80, weight average molecular weight: 100,000 g / mol) and 3.0 wt % of other additives (VC:1,3-PS:Esa = 1.5:0.5:1 weight ratio) were added to prepare a non-aqueous electrolyte for a lithium secondary battery (see Table 1 below).
[0122] [ka]
[0123] Comparative Example 3. A non-aqueous electrolyte solution for a lithium secondary battery and a lithium secondary battery including the same were manufactured in the same manner as in Example 1, except that LiPF was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 5.0 wt % of the oligomer represented by Chemical Formula 5 and 3.0 wt % of other additives (weight ratio of VC:1,3-PS:Esa = 1.5:0.5:1) were added to prepare a non-aqueous electrolyte solution for a lithium secondary battery (see Table 1 below).
[0124] [Table 1]
[0125] Experimental example Experimental Example 1. Evaluation of high temperature cycle characteristics (1) The lithium secondary batteries prepared in Examples 1 to 3 and the lithium secondary batteries prepared in Comparative Examples 1 to 3 were each charged to 4.2 V at 45° C. under constant current / constant voltage conditions at a 0.33 C rate, and then discharged to 3 V under constant current conditions at a 0.33 C rate, which constituted one cycle. The discharge capacity and resistance after one cycle were measured.
[0126] Next, after 100 cycles of charge and discharge under the same conditions, the capacity retention rate (%) and the resistance increase rate (%) were measured. The capacity retention rate (%) was calculated using the following formula (1), and the resistance increase rate (%) was calculated using the following formula (2). The measurement results are shown in Table 2 below.
[0127] [Formula 1] Capacity retention rate (%) = (discharge capacity after 100 cycles / discharge capacity after 1 cycle) x 100
[0128] [Formula 2] Resistance increase rate (%) = {(resistance after 100 cycles - resistance after 1 cycle) / resistance after 1 cycle} x 100
[0129] Experimental Example 2. Evaluation of high temperature cycle characteristics (2) The lithium secondary batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were each charged to 4.2 V at 45° C. under constant current / constant voltage conditions at a rate of 0.33 C and then discharged to 3 V under constant current conditions at a rate of 0.33 C, which constituted one cycle, and the initial thickness was measured. Then, after 100 charge / discharge cycles under the same one-cycle conditions, the thickness was measured and the volume increase rate was calculated. The results are shown in Table 2 below.
[0130] [Table 2]
[0131] Referring to Table 2, it can be seen that the capacity retention rate (%), resistance increase rate (%), and volume increase rate (%) after 100 cycles at high temperature (45°C) of the secondary batteries of Examples 1 to 3 of the present invention were improved compared to the secondary batteries of Comparative Examples 1 to 3.
[0132] Experimental Example 3: Evaluation of volume increase rate after high-temperature storage The lithium secondary batteries prepared in Examples 1 to 3 and the lithium secondary batteries prepared in Comparative Examples 1 to 3 were each charged to 4.2 V at room temperature (25°C) under constant current / constant voltage conditions at a 0.33 C rate, and then discharged to a depth of discharge (DOD) of 50% to achieve a SOC of 50%. After that, the batteries were discharged at a 2.5 C rate for 10 seconds, and the initial volumes were measured.
[0133] Then, after storing at 60° C. for 8 weeks, the volume of each lithium secondary battery after high-temperature storage was measured to confirm the volume increase rate, and the results are shown in Table 3 below.
[0134] [Table 3]
[0135] Referring to Table 3, it can be seen that the secondary batteries of Examples 1 to 3 of the present invention had a reduced volume increase rate (%) after high-temperature storage compared to the secondary batteries of Comparative Examples 1 to 3.
[0136] Experimental Example 4: Evaluation of metal elution amount The lithium secondary batteries prepared in Examples 1 to 4 and the lithium secondary batteries prepared in Comparative Examples 1 to 3 were each fully charged to 100% SOC (4356 mAh) at a voltage of 4.45 V. The batteries were then heated from 25°C to 60°C at a rate of 0.7°C / min and stored at 60°C for 8 weeks. After that, the batteries were charged at 0.33C and discharged at 0.33C, and decomposed in a fully discharged state. The amounts of Ni, Co, and Mn deposited on the negative electrode were analyzed (ICP-OES, Perkin Elmer, AVIO 500), and the results are shown in Table 4 below.
[0137] [Table 4]
[0138] Referring to Table 4, it can be seen that the secondary batteries of Examples 1 to 4 of the present invention had a reduced amount of metal ion elution after high-temperature storage compared to the secondary batteries of Comparative Examples 1 to 3. This result shows that the lithium secondary battery using the nonaqueous electrolyte of the present invention has an improved effect of inhibiting metal elution.
[0139] Experimental Example 5. Evaluation of recovery capacity The lithium secondary batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were each fully charged to 100% SOC (4356 mAh) at a voltage of 4.45 V. Then, the batteries were heated from 25°C to 60°C at a temperature increase rate of 0.7°C / min and stored at 60°C for 8 weeks. After that, the batteries were charged at 0.33C and discharged at 0.33C to measure the recovered capacity, and the results are shown in Table 5 below.
[0140] [Table 5]
[0141] Referring to Table 5, it can be seen that the secondary batteries of Examples 1 to 4 of the present invention have improved recovered capacity (%) compared to the secondary batteries of Comparative Examples 1 to 4. On the other hand, in the case of the secondary battery of Example 4, which contained a slightly larger amount of additive, it was found that the recovered capacity (%) was lower than that of the secondary batteries of Examples 1 to 3 due to an increase in the internal resistance of the battery.
[0142] Experimental Example 6. Evaluation of anion stabilization The non-aqueous electrolytes prepared in Examples 1 to 4 and the non-aqueous electrolytes prepared in Comparative Examples 1 to 3 were stored at 45°C for 1 week, and then the amount of HF was measured using a Metrohm (785 DMP Titrino) to compare the anion stabilization effects. The results are shown in Table 6 below.
[0143] [Table 6]
[0144] Referring to Table 6, it can be seen that the anion stabilizing concentration (ppm) of the secondary batteries of Examples 1 to 4 of the present invention is lower than that of the secondary batteries of Comparative Examples 1 to 3. That is, it is believed that the oligomer used as an additive in the present invention stabilizes the thermal decomposition product of the lithium salt or the anion dissociated from the lithium salt by forming a complex with the thermal decomposition product of the lithium salt or the anion dissociated from the lithium salt, thereby reducing the HF concentration in the electrolyte.
Claims
1. A lithium salt; A non-aqueous organic solvent; An oligomer including a repeating unit derived from a monomer represented by the following chemical formula 1 and a repeating unit derived from a monomer represented by the following chemical formula 2: A non-aqueous electrolyte for a lithium secondary battery comprising: 【Chemistry 1】 (In the above Chemical Formula 1, R' is hydrogen or an alkyl group having 1 to 3 carbon atoms; R 1 is an alkylene group having 1 to 20 carbon atoms. 【Chemistry 2】 (In the above Chemical Formula 2, R″ is hydrogen or an alkyl group having 1 to 3 carbon atoms; R 2 is a direct bond or an alkylene group having 1 to 5 carbon atoms, A is an aromatic hydrocarbon group or a heteroaromatic hydrocarbon group.
2. The nonaqueous electrolyte for a lithium secondary battery according to claim 1 , wherein the oligomer is represented by the following Chemical Formula 3: 【Chemistry 3】 (In the above Chemical Formula 3, R' and R'' are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; R 1 is an alkylene group having 1 to 20 carbon atoms, R 2 is a direct bond or an alkylene group having 1 to 5 carbon atoms, A is an aromatic or heteroaromatic hydrocarbon group; The molar ratio of m:n is 1:99 to 99:
1.
3. The R 1 is an alkylene group having 1 to 10 carbon atoms, The R 2 is an alkylene group having 1 to 3 carbon atoms, the aromatic hydrocarbon group is at least one of benzene, naphthalene, and anthracene; 3. The nonaqueous electrolyte for a lithium secondary battery according to claim 2, wherein the heteroaromatic hydrocarbon group is at least one of pyrrole, imidazole, pyridine, pyrazine, pyrimidine, pyridazine, 1,2,3-triazine, 1,2,4-triazine, and 1,3,5-triazine.
4. The R 1 is an alkylene group having 1 to 5 carbon atoms, the aromatic hydrocarbon group is benzene; 3. The nonaqueous electrolyte for a lithium secondary battery according to claim 2, wherein the heteroaromatic hydrocarbon group is at least one of pyrrole, imidazole, pyridine, pyrazine, pyrimidine, and pyridazine.
5. The nonaqueous electrolyte for a lithium secondary battery according to claim 2, wherein the oligomer is at least one selected from the group consisting of oligomers represented by the following Chemical Formula 3-1 and Chemical Formula 3-2. 【Chemistry 4】 (In the above Chemical Formula 3-1, The molar ratio of m1:n1 is 1:99 to 99:
1. 【Chemistry 5】 (In the above Chemical Formula 3-2, The molar ratio of m2:n2 is 1:99 to 99:
1.
6. 2. The non-aqueous electrolyte for a lithium secondary battery according to claim 1, wherein the oligomer is contained in an amount of 0.1 to 25% by weight based on the total weight of the non-aqueous electrolyte for a lithium secondary battery.
7. 2. The non-aqueous electrolyte for a lithium secondary battery according to claim 1, wherein the oligomer is contained in an amount of 0.5 to 20% by weight based on the total weight of the non-aqueous electrolyte for a lithium secondary battery.
8. 2. The nonaqueous electrolyte solution for a lithium secondary battery according to claim 1, further comprising at least one other additive selected from the group consisting of cyclic carbonate-based compounds, halogen-substituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based or phosphite-based compounds, borate-based compounds, nitrile-based compounds, benzene-based compounds, amine-based compounds, silane-based compounds, and lithium salt-based compounds.
9. a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator interposed between the negative electrode and the positive electrode; The nonaqueous electrolyte for a lithium secondary battery according to any one of claims 1 to 8, A lithium secondary battery comprising:
10. The lithium secondary battery according to claim 9 , wherein the positive electrode active material comprises a lithium composite metal oxide represented by the following Chemical Formula 4: [Chemical formula 4] Li 1+a Ni x Co y M 1 z M 2 w O 2 (In the above Chemical Formula 4, M 1 is Mn, Al, or a combination thereof; M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, Mg, Ca, and Sr, and 0≦a≦0.5, 0<x≦1.0, 0<y≦0.4, 0<z≦0.4, and 0≦w≦0.1.)
Citation Information
Patent Citations
Nonaqueous electrolyte and secondary battery
JP2012138314A
Gel polymer electrolyte composition and lithium secondary battery containing the same
JP2015528987A
Electrolyte composition for lithium secondary battery and lithium secondary battery containing same
JP2021501451A
Thermosetting electrolyte composition for lithium secondary battery, gel polymer electrolyte prepared therefrom, and lithium secondary battery including the electrolyte
US20210257660A1
Electrolyte Solution For Lithium Secondary Battery and Lithium Secondary Battery Including the Same
US20210328266A1